The first six books of the Elements of Euclid : in which coloured diagrams and symbols are used instead of letters for the greater ease of learners - Byrne, Oliver; Euclid; Oechslin, Werner (Köln : Taschen, 2013)
Nearly a century before Mondrian made geometrical red, yellow, and blue lines famous, 19th century mathematician Oliver Byrne employed the color scheme for the figures and diagrams in his most unusual 1847 edition of Euclid's Elements. This title deals with this remarkable example of Victorian printing of the 19th century.
Text of facsimile in English; essays in English, French and German ; Essay by Werner Oechslin.
Originally published: London, William Pickering, 1847.
Text in English, French and German.
boek
Keywords: Euclides; Byrne, Oliver; Geometry